Ответ:
Пошаговое объяснение:
0,8(0,5+2х)=2х+0,4
0,4 + 1,6x = 2x + 0,4
2x - 1,6x = 0,4 - 0,4
0,4x = 0
x = 0
\\\\\\\\\\\\\\\\\\\\\
по просьбе
0,2(х-3)-1=0,5(х+3)-0,4
0,2x - 0,6 - 1 = 0,5x + 1,5 - 0,4
0,2x - 1,6 = 0,5x + 1,1
0,5x - 0,2x = -1,6 - 1,1
0,3x = -2,7
x = -2,7 : 0,3
x = -9
х = 0
0,4 + 1,6х = 2х + 0,4
1,6х - 2х = 0,4 - 0,4
-0,4х = 0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
0,8(0,5+2х)=2х+0,4
0,4 + 1,6x = 2x + 0,4
2x - 1,6x = 0,4 - 0,4
0,4x = 0
x = 0
\\\\\\\\\\\\\\\\\\\\\
по просьбе
0,2(х-3)-1=0,5(х+3)-0,4
0,2x - 0,6 - 1 = 0,5x + 1,5 - 0,4
0,2x - 1,6 = 0,5x + 1,1
0,5x - 0,2x = -1,6 - 1,1
0,3x = -2,7
x = -2,7 : 0,3
x = -9
= -9
Ответ:
х = 0
Пошаговое объяснение:
0,8(0,5+2х)=2х+0,4
0,4 + 1,6х = 2х + 0,4
1,6х - 2х = 0,4 - 0,4
-0,4х = 0
х = 0